Assessment of soil quality parameters and yield of rice cultivars in Melaleuca cajuputi agroforestry system - Priyono Suryanto; Taryono TARYONO; Supriyanta SUPRIYANTA; Dody Kastono; Eka Tarwaca Susila Putra; Suci Handayani; MUHAMMAD HABIB WIDYAWAN; Taufan Alam (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Suryanto P, Taryono, Supriyanta, Kastono D, Putra ETS, Widyawan MH, Alam T. 2020. Assessment of soil quality parameters and yield of rice cultivars in Melaleuca cajuputi agroforestry system. Biodiversitas 21: 3463-3470.  Interactions between rice cultivars and soil quality parameters rises problems in the attempt of increasing rice yield. The objective of this study was to assess soil quality parameters that affect the yield of 15 rice cultivars in an agroforestry system of ‘kayu putih’ (Melaleuca cajuputi) situated in Menggoran forest, Yogyakarta, Indonesia which have three soil types namely Lithic Haplusterts, Ustic Epiaquerts, and Vertic Haplustalfs. The observation was conducted on 21 soil quality parameters and yield of rice cultivars. The data were analyzed by using ANOVA, factor analysis, and stepwise regression. The highest yield of rice per hectare was attained by GM 28 in Ustic Epiaquerts with 6.493 tons ha-1, while Situ Patenggang and GM 28 in Vertic Haplustalfs as high as5.549 and 5.401 tons ha-1, respectively, and Situ Patenggang in Lithic Haplusterts as high as 4.893 tons ha-1. Soil quality parameters that had significant effect on the yield of rice cultivars were Clay, SMC, pH, SOC, N, Mg, Fe, Fg, and Bae. We suggested that rice cultivars recommendations for Lithic Haplusterts, Ustic Epiaquerts, and Vertic Haplustalfs are Situ Patenggang, Situ Patenggang or GM 28, and GM 28, respectively, in addition to fertilization based on limiting factors of each rice cultivars.